Contrast-enhanced ultrasonographic findings in torsion of the appendix testis or epididymis in children: a case series - Fukuzawa, Hiroaki; Minoda, Naoki; Okamoto, Mitsumasa; Tsuruno, Yudai; Watanabe, Aya (Journal of Medical Ultrasonics, 2024)
Purpose Torsion of the appendix testis or epididymis is a cause of acute scrotum in children. Ultrasonography with color Doppler is the first-choice modality for diagnosis. However, this method requires skill and experience to make a diagnosis with confidence. Recently, contrast-enhanced ultrasonography for diagnosis in various fields has been reported. However, to our knowledge, there has been no report of this method being used to diagnose torsion of the appendix testis or epididymis. The purpose of this study was to retrospectively examine contrast-enhanced ultrasonographic findings in torsion of the appendix testis or epididymis. Methods Patients who underwent contrast-enhanced ultrasonography for torsion of the appendix testis or epididymis at our institution between April 2010 and April 2023 were enrolled in this study ( n = 12). Contrast-enhanced ultrasonography findings of the affected appendage and the testis parenchyma were examined retrospectively. Results The parenchyma of the testes was notably enhanced in all the cases. However, 9 of the 12 cases showed that the appendage with torsion was not enhanced at all. In the remaining three cases, only slight enhancement was seen. Nevertheless, it was notably less than that of the parenchyma of the testis. Conclusion Our findings indicated that contrast-enhanced ultrasonography may be an easy and reliable method for diagnosing torsion of the appendix testis or epididymis.